Timings and presentation profile of adult inguinal hernias at a district hospital set up in central India - Jain, Rajiv; Jain, Anurag; Gupta, Hariom (International Surgery Journal, 2019)
Background: Present study outlines experiences related to inguinal hernia presentation at a district hospital set up with respect to duration of time, mode of presentation and an effort have been made to analyse factors influencing them. Methods: Descriptive, epidemiological, prospective type of study design was adopted. Adult patients above 20 years presenting with inguinal hernia at District Hospital Sehore, Madhya Pradesh, India, were included in study; considering inclusion and exclusion criteria. Time frame of present study was from April 2017 to April 2018. Under proper written consent relevant data was collected on a pro-forma. Variables obtained were statistically analysed and magnitude of problem estimated on the background of available literature. Results: 80 patients were enrolled in the study with mean age of 39.64±09.59 years. Majority were men (98.75%) and farming was main occupation (51.25%). Main complaint was lump above the inguinal crease with pain. Increased pain in lump was the main cause of presentation (100%). Predominance of right sided hernia was noted (60%). Almost 36 patients (45%) were admitted with features of obstruction. Lack of awareness of the disease (41.25%) was commonest reason for late presentation. The most common operative procedure done was Lichtenstein’s hernioplasty. Conclusions: There is a need for health education and awareness among common masses especially from rural sector regarding inguinal hernia as a treatable surgical entity which can become life threatning when entity becomes complicated. Counselling regarding government funded schemes like Ayushman Bharat to be done at grass root level. Primary and community health centres need up gradation with availability of full time surgical expertise.